Effect of Liothyronine Treatment on Dermal Temperature and Activation of Brown Adipose Tissue in Female Hypothyroid Patients: A Randomized Crossover Study - Bjerkreim, Betty Ann; Hammerstad, Sara Salehi; Gulseth, Hanne Løvdal; Berg, Tore Julsrud; Lee-Ødegård, Sindre; Rangberg, Anbjørg; Jonassen, Christine Monceyron; Budge, Helen; Morris, David; Law, James; Symonds, Michael; Eriksen, Erik Fink (Frontiers in Endocrinology, 2021)
Background: Thyroid hormones are essential for the full thermogenic response of brown adipose tissue (BAT) and have been implicated in dermal temperature regulation. Nevertheless, persistent cold-intolerance exists among a substantial proportion of hypothyroid patients on adequate levothyroxine (LT4) substitution. Materials and Methods: To assess if skin temperature and activation of BAT during treatment with liothyronine (LT3) differs from that of LT4 treatment, fifty-nine female hypothyroid patients with residual symptoms on LT4 or LT4/LT3 combination therapy were randomly assigned in a non-blinded crossover study to receive monotherapy with LT4 or LT3 for 12 weeks each. Change in supraclavicular (SCV) skin temperature overlying BAT, and sternal skin temperature not overlying BAT, during rest and cold stimulation were assessed by infrared thermography (IRT). In addition, abundance of exosomal miR-92a, a biomarker of BAT activation, was estimated as a secondary outcome. Results: Cold stimulated skin temperatures decreased less with LT3 vs. LT4 in both SCV (mean 0.009 °C/min [95% CI: 0.004, 0.014]; P<0.001) and sternal areas (mean 0.014 °C/min [95% CI: 0.008, 0.020]; P<0.001). No difference in serum exosomal miR-92a abundance was observed between the two treatment groups Conclusion: LT3 may reduce dermal heat loss. Thermography data suggested increased BAT activation in hypothyroid patients with cold-intolerance. However, this finding was not corroborated by assessment of the microRNA biomarker of BAT activation. ClinicalTrials.gov identifier: NCT03627611